Organocatalytic route to enantioselective synthesis of ceramide trafficking inhibitor HPA-12 - Lalwani, Komal G.; Sudalai, Arumugam (Tetrahedron Letters, 2016)
A new organocatalytic approach to the synthesis of ceramide trafficking inhibitor HPA-12 has been described starting from phenacyl bromide. The strategy involves chiral CBS reduction of gamma-ketoester and proline-catalyzed alpha-amination reaction of aldehyde followed by reduction as the key chirality inducing steps. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: alpha-Amination; CBS reduction; Ceramide; Organocatalytic; Proline